Treatment of patients with Schistosomiasis mansoni: a double blind clinical trial comparing praziquantel with oxamniquine - Luiz Caetano da Silva; José Murilo R. Zeitune; Lucia Maria F. Rosa-Eid; Dirce Mary C. Lima; Rita H. Antonelli; Carlos H. Christo; Amadeo Saez-Alquezar; Adriany de Castro Carboni (Revista do Instituto de Medicina Tropical de São Paulo, 1986)
A double-blind clinical trial involving 120 patients with chronic schistosomiasis was carried out to compare the tolerability and efficacy of praziquantel and oxamniquine. The patients were randomly allocated into two groups. One was treated with praziquantel, 55 mg/kg of body weight CBWT), and the other one with oxamniquine, 15mg/kg bwt, administered in a single oral dose. The diagnosis and the parasitological follow-up was based on stool examinations by quantitative Kato-Katz method and on rectal biopsies. Side-effects — mainly dizziness, sleepness, abdominal distress, headache, nausea and diarrhea — were observed in 87% of the cases. Their incidence, intensity and duration were similar for both drugs but abdominal pain was significantly more frequent after praziquantel intake and severe dizziness was more commonly reported after oxamniquine. A significant increase of alanine-aminotransferase and y-glutamyltransferase was found with the latter drug and of total bilirubin with the former one. A total of 48 patients treated with praziquantel and 46 with oxamniquine completed with negative findings the required three post-treatment parasitological controls — three slides of each stool sample on the first, third and sixth month. The achieved cure rates were 79.2% and 84.8%, respectively, a difference without statistical significance. The non-cured cases showed a mean reduction in the number of eggs per gram of feces of 93.5% after praziquantel and of 84.1% after oxamniquine. This diference also was not significant. Five patients retreated with praziquantel were cured but only one out of three treated a second time with oxamniquine. These findings show that both drugs — despite their different chemical structures, pharmacological properties and mechanisms-of-action — induce similar side-effects as well as a comparable therapeutical efficacy, in agreement with the results reported from analogous investigations.